2021
DOI: 10.1007/s00122-020-03742-6
|View full text |Cite
|
Sign up to set email alerts
|

OsPPR939, a nad5 splicing factor, is essential for plant growth and pollen development in rice

Abstract: Key message P-subfamily PPR protein OsPPR939, which can be phosphorylated by OsS6K1, regulates plant growth and pollen development by involving in the splicing of mitochondrial nad5 introns 1, 2, and 3. Abstract In land plants, pentatricopeptide repeat (PPR) proteins play key roles in mitochondrial group II intron splicing, but how these nucleus-encoded proteins are imported into mitochondria is unknown. To date, a few PPR proteins have been characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In maize ( Zea mays L.), researchers have found that missplicing of U12-type introns in rgh3 can cause aberrant endosperm cell differentiation and proliferation [ 16 ]. In rice ( Oryza sativa ), OsPPR939 plays crucial roles in plant growth and pollen development by splicing introns 1, 2, and 3 of mitochondrial nad5 [ 17 ]. Fruits can be divided into fleshy fruits and dry fruits according to the types of fruit walls [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In maize ( Zea mays L.), researchers have found that missplicing of U12-type introns in rgh3 can cause aberrant endosperm cell differentiation and proliferation [ 16 ]. In rice ( Oryza sativa ), OsPPR939 plays crucial roles in plant growth and pollen development by splicing introns 1, 2, and 3 of mitochondrial nad5 [ 17 ]. Fruits can be divided into fleshy fruits and dry fruits according to the types of fruit walls [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Without support from heterozygous maternal tissues, the response in homozygous seedlings or calli is perhaps weakened or abolished. Thus, small subcomplexes were not observed in the fse5 mutant or rice ppr mutants such as fgr1, flo10 and osppr939 (Hao et al 2019;Wu et al 2019;Zheng et al 2021).…”
Section: Discussionmentioning
confidence: 94%
“…OsActin1 was used as an internal control for data normalization. The values are the means ± SDs Homozygous immature dek35 kernels were used to extract crude mitochondria for BN-PAGE, whereas homozygous seedlings or calli (−/−) are usually used in the case of rice (Hao et al 2019;Wu et al 2019;Zheng et al 2021). In this study, homozygous fse5 seedlings were used for BN-PAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants of these PPR genes lead to complete abolishment of intact complex I and result in severe seed developmental defects, highlighting the importance of complex I for seed development. By contrast, only a few proteins in rice were identified to function in mitochondrial intron splicing, such as OsPPR939 for nad5 intron 1, 2, 3 40 and RL1 for nad4 intron 1 41 . Here, we identified SOP10 and showed it participates in splicing of nad4 and nad5 intron1 and RNA editing of nad2 and nad6 .…”
Section: Discussionmentioning
confidence: 99%